Calibration of AVHRR Data Generated by the Instrument on-board TIROS-N Using Ocean and Cloud Views - Cracknel, Arthur P.; Busu, Ibrahim (1997)
Remote sensing images of the Earth have been regarded by many as an important source of data for environmental studies. In order to produce good quality data, all known errors should be removed or eliminated before any of the data are used, especially for time-dependent applications. Over the years a number of post-launch calibration methods and procedures have been suggested and used, particularly for the later spacecraft in the series; each of these has some advantages and disadvantages over the others. This paper reviews a post-launch calibration method which has been established using ocean and cloud views as the main calibration targets; it then applies this method to data from the earlier spacecraft in the series which are no longer in operation.